A real-time business process decisions support planning system for mould industry: a case study. (6th January 2009) - Leung, Y.K.; Choy, K.L.; Kwong, C.K.; Poon, T.C.; , Y.Y. Cheung
Mould manufacturing is an important part of the product development process. Some products require several thousands of pressed moulds and fitting moulds to manufacture different parts of finished goods. Hence, moulds significantly affect the quality of finished goods. The process of manufacturing moulds is complicated and time-consuming and requires the investment of capital in items such as specific machines, staff training, time, etc. Due to the shorter lead times that are being demanded by customers, mould manufacturers are finding ways to reduce their production time. In the past decade, much research has focused on the improvement of the business process of mould manufacturing. In this paper, a Real-time Business Process Decisions Support (RBPDS) system in the mould industry is proposed. The system incorporates Radio Frequency Identification (RFID) technology and Case-based Reasoning (CBR). The system is used to track shop floor production information in real time and provide decision support for planning. It provides instant decision support for production planning, cost estimation and production precautions. The system is applied to a company to enhance its decision support process. The case study shows that there is a significant improvement in various business processes when they are supported by the system.